Software Architecture Hour Architecture and Security with Aaron Bedra - Ford, Neal; Bedra, Aaron (O'Reilly Media, Inc., 2021)
Join us for a special conversation on software architecture with Neal Ford and security pro Aaron Bedra, covering the fascinating aspects of the discipline, interesting convergence areas, and insights on how to approach the most challenging aspects of building and managing evolving architectural needs. This is your chance to ask Neal and Aaron anything you want about architecture or their own career journeys. They'll spend a few minutes covering the trends in security that are influencing architecture, then tell you what you need to know to stay ahead of the curve. What you'll learn-and how you can apply it Understand how to build a culture of security compliance See what's coming next with software architecture This training course is for you because ... You want the chance to ask Neal Ford and Aaron Bedra your questions around long-term cybersecurity and your architecture. You're looking for ways to improve security to support your businesses goals. You want to learn about a holistic approach to security. Prerequisites Come with your questions for Neal Ford and Aaron Bedra Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Read Fundamentals of Software Architecture (book) Read Building Microservices, second edition (book) Read Container Security (book) Read Practical Cloud Security (book) Attend the Software Architecture Superstream: Mastering Your Microservices Stack (May 19) Attend Architecture: The Hard Parts (live online training course with Mark Richards and Neal Ford) Watch Software Architecture Superstream Series: Domain-Driven Design and Event-Driven Microservices (recorded Superstream event, 3h 29m)
Online resource; Title from title screen (viewed April 7, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos